People and Animals in Lithuanian Folktales: the Didactical and Psychological Aspects - Sadauskienė, Jurga (Tautosakos darbai, 2018)
The purpose of the article is revealing the great variety of relationships between humans and animals in the traditional Lithuanian folktales in order to understand the meaning of the animal motives in this folklore genre. Analysis of the ethical, pedagogical and psychological aspects of the tales rests on the printed and archived materials from the 19th – 20th century. The author discusses the instances of clashing and matching perspectives between the folklore-centered, psychological, and culture-oriented views on the traditional narratives and on the worldview that these narratives reflect. Representations of both the wild animals, birds and reptiles, and the domesticated ones in the Lithuanian fairy tales and animal tales are symbolical rather than realistic, thus encouraging to view these narratives as essentially meant for upbringing or psychotherapy rather than natural education. According to the emotional, ethical and pedagogical value of relationships between the protagonist and the animals, the folktale motives fall into several groups:a. relations based on fear (folktales prohibiting to hurt the totemic animals);b. overcoming of fear and hostility (folktales describing marriage with animals);c. empathy (folktales describing people saving and caring for the animals, and therefore experiencing great success);d. acquiring protection (folktales describing animals sacrificing themselves for the benefit of the protagonist);e. animals endowed with authority in the eyes of the humans (folktales revealing special powers and capacities of the animals, which alone enable the humans to achieve their aims; these tales reveal dependence of people on nature);f. narratives enhancing emotional consciousness (tales of animals and formula tales dedicated to the youngest children and teaching them strategies of safe behavior as well as encouraging their emotional self-awareness);g. hostility (stories derived from the medieval animal epos);h. pragmatism and economical attitude (folktales describing animals as sources of profit rather than self-contained characters).In conclusion, the author assumes that literary tradition must have had minimum impact on the ancient Lithuanian folktales and their worldview in particular, since they do not antagonize the natural and the human world. Contrary to the view expressed by the French cultural historian Robert Darnton maintaining that French tales essentially have been harsh and cynical, the majority of the Lithuanian tales merit recognition for their positive view of the world, for bringing up educational examples, for pedagogical intentions and the general concept that rightful behavior deserves an appropriate reward. Having discussed the psychoanalytic interpretations of folktales, the author assumes that animals in the oldest versions of the Lithuanian folktales play the role of the superego rather than id. This allows to maintain that respectful attitude towards animals was inherent in the culture of the ancient peoples, particularly the peasants, being “discovered” in the literary tradition as late as the end of the 19th century.
Keywords: folktale; animals; traditional pedagogics; cultural psychology; Lithuanian worldview